Contratos de trabalho flexível nos sistemas jurídicos italiano e brasileiro - Ludovico, Giuseppe; Levi, Alberto; Dorea Martinez Carreiro, Luciano; Nahas, Thereza Christina (Studi Italo-Brasiliani di Diritto del Lavoro e della Previdenza Sociale, 2023)
The second and third volumes of the series "Italo-Brazilian Studies of Labour Law and Social Security" are dedicated to the analysis of the discipline of flexible labour contracts in force in the two legal systems. With the participation of important scholars from both countries, the volumes offer a comprehensive examination of the evolution of flexibility in the Italian and Brazilian labour markets through an in-depth examination of the main forms of relationships other than the traditional but less central one of full-time and open-ended employment. The publication of the volume in Italian and Portuguese is intended to facilitate, in keeping with the aim of the Series, the circulation of legal knowledge between the two countries.